2009
DOI: 10.2353/ajpath.2009.080872
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Deficiency Impairs Matrix Metalloproteinase-9 Activity and Disrupts Leukocyte Migration in Hepatic Ischemia/Reperfusion Injury

Abstract: Matrix metalloproteinase 9 (MMP-9) is a critical mediator of leukocyte migration in hepatic ischemia/ reperfusion (I/R) injury. To test the relevance of inducible nitric oxide synthase (iNOS) expression on the regulation of MMP-9 activity in liver I/R injury, our experiments included both iNOS-deficient mice and mice treated with ONO-1714, a specific iNOS inhibitor. The inability of iNOS-deficient mice to generate iNOS-derived nitric oxide (NO) profoundly inhibited MMP-9 activity and depressed leukocyte migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 54 publications
(96 reference statements)
4
70
1
Order By: Relevance
“…Furthermore, in the current study, we found that the activation of MMP-9 in KCs was decreased markedly in TGF-β-treated animals. Taken together with the findings in other IRI models [35,36], the results support a protective role of TGF-β in liver IRI.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, in the current study, we found that the activation of MMP-9 in KCs was decreased markedly in TGF-β-treated animals. Taken together with the findings in other IRI models [35,36], the results support a protective role of TGF-β in liver IRI.…”
Section: Discussionsupporting
confidence: 85%
“…The role of iNOS-derived NO in I/R injury is not straightforward because studies reported on its protective [141], harmful [142] or no [141, 143] effects. These studies differ in the length of ischemia or reperfusion, which may account for the observed different roles of iNOS in liver I/R injury.…”
Section: No and Liver Diseasesmentioning
confidence: 99%
“…Mouse neutro phils were isolated from bone marrow (Hamada et al, 2009). In brief, femurs and tibias were harvested and stripped of all muscle and sinew.…”
Section: Huvec-grown Transwell Migration Of Human T Cells and Neutropmentioning
confidence: 99%